Partial differential equations for scientists and engineers - Farlow, Stanley J., 1937- (Dover books on advanced mathematics., 1993)
This highly useful text for students and professionals working in the applied sciences shows how to formulate and solve partial differential equations. Realistic, practical coverage of diffusion-type problems, hyperbolic-type problems, elliptic-type problems and numerical and approximate methods. Suggestions for further reading. Solution guide available upon request. 1982 edition.